An S-adenosyl Methionine Synthetase (SAMS) Gene from Andropogon virginicus L. Confers Aluminum Stress Tolerance and Facilitates Epigenetic Gene Regulation in Arabidopsis thaliana - Ezaki, Bunichi; Higashi, Aiko; Nanba, Norie; Nishiuchi, Takumi (Frontiers in Plant Science, 2016)
Candidate clones which conferred Al tolerance to yeast transformants (TFs) were obtained from a cDNA library derived from a highly Al-tolerant poaceae, Andropogon virginicus L. One such clone, AL3A-4, encoded an S-adenosyl methionine synthetase (SAMS) gene. A full-length cDNA was obtained by 5’-RACE, designated AvSAMS1, and introduced into Arabidopsis thaliana to investigate its biological functions under Al stress. Two TF plant lines both showed higher tolerance than the Col-0 ecotype (non-TF) not only for Al stress, but also for Cu, Pb, Zn and diamide stresses, suggesting the AvSAMS1 was a multiple tolerance gene. More than 40 of A. thaliana Al response-genes (Al induced genes and Al repressed genes) were selected from microarray results and then used for investigations of DNA or histone methylation status under Al stress in Col-0 and the AvSAMS1 TF line. The results indicated that Al stress caused alterations of methylation status in both DNA and histone H3 (H3K4me3 and H3K9me3) and that these alterations were different between the AvSAMS1 TF and Col-0, suggesting the differences were AvSAMS1-gene dependent. These results suggested the existence of AvSAMS1-related epigenetic gene-regulation under Al stress.